Switch or Stay: Unraveling the Loyalty Puzzle in Nepal’s Telecom Industry - G.C, Prakash (Devkota Journal of Interdisciplinary Studies, 2025)
The primary aim of this research is to explore the relationship between customer satisfaction and customer loyalty within Nepal’s mobile telecommunications sector. This industry has seen intensified competition in recent years, driven by the emergence of new service providers offering competitive pricing strategies, extensive promotional campaigns, improved network coverage, and enhanced customer engagement. A total of 384 participants were surveyed for this study. Among the five variables examined – namely, Service Excellence, Pricing Strategy, Switching Barriers, Brand Equity, and Responsiveness – it was discovered that Responsiveness and Brand Equity demonstrate a strong, positive influence on customer loyalty. However, this research is not without limitations. The data collection was confined to the Kathmandu Valley, which restricts the broader applicability of the findings to the nationwide user base of mobile services. The relatively limited geographical scope and the sample representation mean that results should be interpreted with caution when applied to the wider population. In conclusion, it is imperative for mobile network providers to recognize and act upon the dynamics between customer satisfaction and loyalty. Striking a balance between retaining existing users and attracting new subscribers remains a significant strategic undertaking in Nepal’s evolving telecom landscape.